Normal aproximation when sampling from bounded symmetric distributions - Clavijo M., Jairo; Ospina, David (Revista Colombiana de Estadística, 1995)
This paper introduces a basic methodology which, based on simulations, determines the mínimum sample size necessary to use the normal approximation when estimating means from population with bounded symmetric distributions.